Efeito da atividade física na sensibilidade à insulina e no sinal insulínico em ratos com doença periodontal - Mota, Max Sander de Oliveira da [UNESP] (2014)
Studies have shown that there is a correlation between Diabetes Mellitus (DM) and Periodontal Disease (PD) in a way that people with DM present higher prevalence and severity of PD, when compared with healthy people. It is also observed that among people with PD there is an increased prevalence of Diabetes. Previous studies in our laboratory showed that PD induces alterations in insulin signaling and insulin resistence. Several studies showed that exercise can promote improvements in insulin sensitivity. Knowing that DP reduces insulin sensitivity and signaling, this study investigated if physical exercise can revert or improve this condition in rats with PD. Therefore, it was assessed in rats with PD submitted or not to exercise: 1) insulin sensitivity; 2) glycemia, insulinemia; 3) TNF-α and IL-6 plasma levels; 4) cholesterolemia and triglyceridemia; 5) insulin receptor substrate pp185 (IRS-1/IRS-2) tyrosine and serine phosphorylation status. Therefore, 80 male Wistar rats (two-month-old) were distributed into four groups: 1) sedentary control group without PD (CNS); 2) exercised control group without PD (CNEx); 3) sedentary group with PD (DPS); 4) exercised group with PD (DPEx). In those groups with PD, the disease was induced by ligating silk thread on the lower first molars. After that, it was assessed food ingestion (three times a week) and body weight (once a week) of rats in all groups. In the 28th day after the disease induction, the resistance training began. After 12 weeks of training, the experiments were performed. Statistical analysis was performed by analysis of variance (ANOVA) followed by Tukey's test. Significance value adopted was of 5%. No significant difference was observed in glycemia of the studied groups. DPS had higher insulin levels when compared to CNS, CNEx and DPEX. DPS showed increased insulin...